Toleransi Beragama Siswa Dalam Interaksi Sosial di Sekolah Menengah Kejuruan Negeri 2 Singosari Malang - Siska Saputri; Rosichin Mansur; Ibnu Jazari (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to determine the issues of religious tolerance in social interactions with the focus studied are as follows: (1) the condition of diversity in Singosari State Vocational School 2 in addressing existing religious differences, tolerance of students in social interactions on religious people in Singosari Vocational High School 2. The estimator used is a qualitative approach, while the type of research is a case study. Data collection is done by participatory observation, unstructured interviews, and documentation. Data analysis techniques use three stages of Miles and Humberman, namely data reduction, data display, and conclusion drawing / verification. While checking the validity of the data by triangulation. The results of the study show that the condition of religious tolerance at Singosari State Vocational High School 2 is good enough that students are able to tolerate respect, respect and receive well for differences and students are able to override differences in interaction. The supporting factors of tolerance that exist in this school are because planting or religious foundations are well-owned by students as well as the policies of schools that are able to protect and be fair with the majority of religious or minority religious students in schools. The inhibiting factor is the lack of time to study Christianity compared to the time of sufficient Islamic studies, lack of understanding or understanding of students that in tolerating each religion has its own limitations, especially those contained in Islamic religion.